An Ambiguity of Constitutional Law Major at the Faculty of Sharia of Islamic Higher Education Institutions in Indonesia - Zainuddin, Zainuddin; Yustiloviani, Yustiloviani; Raus, Afrian; Mauliddin, Mauliddin (Mazahib, 2019)
This article examines the problem of majoring Constitutional Law at the Faculty of Sharia in Islamic Higher Education Institutions in Indonesia. There is an ambiguity of the essence of Constitutional Law at the Faculty of Sharia whose Siyasah (simply translated into Constitutional Law) as a major. The core subjects of constitutional law are legal studies on basic law aka constitution. Meanwhile, the essence of siyasah is politics. Does this ambiguity occur only in the nomenclature or also in its implementation as well that include the department’s vision, mission, curriculum, competency, and profile of graduates? This study was a library research which employs a qualitative data analysis towards the so-called siyasa department’s vision and mission documents, curriculum documents, textbooks assigned, teaching materials, research journals, and websites across Islamic Higher Education Institutions in Indonesia. It found that there has been an ambiguity in some Departments of Constitutional Law at the Faculty of Sharia both in the Department nomenclature and in its implementation, such as vision, curriculum, student final assignments, student competency, and profile of graduates. This ambiguity lies in which specialization aims at by the major: law in general, politics, or constitution? On the one hand, the objective of the department is to train the students with legal studies focusing on Islamic Constitutional Law (Qanun Dusturi al-Islamy). On the other hand, the courses on politics are prominent too while there is not enough subjects on the Islamic Constitutional Law. It thus suggests the siyasa Department management across the Faculty of Sharia in Indonesia reorient their vision and mission and match them with their curriculum and programs.Keywords: Ambiguity, constitutional law, Faculty of Sharia